2017
DOI: 10.1016/j.ifset.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal hybrid drying of fruits and vegetables: A review of current technologies

Abstract: Fruits and vegetables are very perishable commodities that have enormous industrial and commercial importance. To preserve its quality attributes, increase shelf life, and reduce transport weight, fruit and vegetable can be processed by drying. Over the years, conventional drying techniques have been widely applied, both industrially and commercially for the processing and preservation of fruits and vegetables. However, most of the conventional techniques are time and energy consuming, and affect important qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 80 publications
0
41
0
5
Order By: Relevance
“…The shrinkage evolution of agricultural food materials during the drying process is a common phenomenon directly affecting the final product's overall quality (Onwude et al, ; Onwude, Hashim, Janius et al, 2016). Drying method, drying condition, and MC affect shrinkage and the resultant bulk density of the seeds (Koua, Koffi, & Gbaha, ; Serowik et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The shrinkage evolution of agricultural food materials during the drying process is a common phenomenon directly affecting the final product's overall quality (Onwude et al, ; Onwude, Hashim, Janius et al, 2016). Drying method, drying condition, and MC affect shrinkage and the resultant bulk density of the seeds (Koua, Koffi, & Gbaha, ; Serowik et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…PEF employs very high voltage pulses (1 to 80 KV/cm) for fractions of a second such as millisecond or microsecond; the voltage and the treatment duration can be adjusted according to the requirements. Besides microbial inactivation, PEF is also applied for alternative purposes such as enzyme inactivation (Onwude et al, 2017), and to increase extraction yield (Puértolas & Martínez De Marañón, 2015;Yan, He, & Xi, 2017). In relation to proteins, PEF has been noted to alter the structural features of proteins; for example, a PEF treatment of 35 KV/cm for 40 μs induces vibrational changes on the bonded side of amino acid chains, altering β-sheets and β-turns suggesting the denaturation of the protein (Liu, Zeng, Deng, Yu, & Yamasaki, 2011).…”
Section: Novel Processing Techniquesmentioning
confidence: 99%
“…Various combinations were tested such as microwave added with spouted fluidized bed system of drying which improved the drying uniformity. Onwude et al () reported that combinations of nonthermal source and convective hot‐air system of drying is as efficient tool in processing (drying) as ultrasound, ultraviolet, and pulse electric field assisted with convective hot‐air drying. In result of various evaluation studies, hybrid solar system of dryers developed were found feasible and economical; such as (Pangavhane & Sawhney, ) reported hybrid solar dryer (HSD) developed for grapes drying, Boughali et al () tested HSD for slices of tomatoes, (Amer, Hossain, & Gottschalk, ) reported ripe banana drying through HSD in such a way that solar energy stored during sunshine period in water and used in cool nights when HSD operated.…”
Section: Modern Drying Techniquesmentioning
confidence: 99%
“…Similarly, this system is more energy-efficient, reduces the duration of processing, cost effective, and easy to operate(Onwude et al, 2017). Various combinations were tested such as microwave added with spouted fluidized bed system of drying which improved the drying uniformity Onwude et al (2017). reported that combinations of nonthermal source and convective hot-air system of drying is as efficient tool in processing (drying) as ultrasound, ultraviolet, and pulse electric field assisted with convective hot-air drying.…”
mentioning
confidence: 99%